Carotid stenosis with impaired brain flow reserve is associated with an increased risk of stroke in on-pump cardiovascular surgery. (26th February 2018) - Tsuda, Kazumasa; Shiiya, Norihiko; Washiyama, Naoki; Yamashita, Katsushi; Ohkura, Kazuhiro; Takahashi, Daisuke; Kando, Yumi; Natsume, Kayoko; Yamanaka, Ken; Takeuchi, Yuki
Abstract: OBJECTIVES: To prevent haemodynamic stroke during cardiovascular surgery in patients with carotid stenosis, we routinely evaluated magnetic resonance angiography and selectively evaluated brain perfusion single-photon emission computed tomography with acetazolamide challenge. Off-pump surgery was preferred when cerebral blood flow reserve was impaired. This strategy's usefulness was investigated. METHODS: Among the 1059 consecutive patients who underwent preoperative carotid screening by magnetic resonance angiography, 84 (7.9%) patients had >50% stenosis; 45 of them underwent brain single-photon emission computed tomography. The severity of cerebral blood flow compromise was estimated by the proportion of Stage 2 area in the affected territory, in which both resting blood flow (<32 ml/min) and flow reserve (<10%) were reduced. RESULTS: Perioperative stroke occurred in 1.7% overall (18/1059), in 6% (5/84) of those with carotid stenosis and in 1.3% (13/975) of those without stenosis ( P  = 0.010). On subgroup analysis, carotid stenosis was associated with an increased risk of stroke in the on-pump surgery group [ n  = 949, 5/59 (9%) with stenosis vs 11/890 (1.1%) without stenosis, P  = 0.002], while it was not in the off-pump group [ n  = 110, 0/25 (0%) with stenosis vs 2/85 (2%) without stenosis, P  = 0.59]. With respect to the role of acetazolamide single-photon emission computed tomography, 2 of the 4 patients with Stage 2 area >10% undergoing on-pump surgery without preceding carotid revascularization developed stroke, while none of the 21 patients with Stage 2 area <10% undergoing on-pump surgery developed stroke ( P  = 0.020). CONCLUSIONS: Carotid stenosis is a risk factor for perioperative stroke in on-pump surgery. Patients with large Stage 2 area (>10%) are at increased risk of perioperative stroke when on-pump surgery is performed.